ATRT-34. TARGETING PRIMARY CILIOGENESIS IN ATYPICAL TERATOID/RHABDOID TUMORS. Issue 2 (22nd June 2018) - Blümel, Lena; Kerl, Kornelius; Qin, Nan; Berlandi, Johannes; Thiel, Katharina; Tegeder, Isabel; Jeibmann, Astrid; Picard, Daniel; Langini, Maike; Stühler, Kai; Meyer, Frauke-Dorothee; Malzkorn, Bastian; et al.
Abstract: Atypical teratoid/rhabdoid tumors (AT/RT) are among the most common malignant brain tumors in infants. Comprehensive genomic studies revealed three distinct molecular subgroups (AT/RT-TYR, -MYC and -SHH). As primary cilia (PC) have already been shown to play a central role in other tumor entities, we aimed to characterize the distribution of PC across AT/RT subgroups and to target primary ciliogenesis in these tumors with dismal prognosis. We performed immunofluorescence to detect PC in AT/RT cell lines (n=2) and primary tumor sections (n=13). The functional role of PC was investigated by knockdown of KIF3A and pharmacological inhibition with Ciliobrevin D in vitro. The relevance of primary ciliogenesis in AT/RT biology was further elucidated using a fly model of SMARCB1 deficiency. We detected PC in both AT/RT cell lines and all primary tumors investigated in this study. Notably, we observed a significant subgroup-specific difference in the proportion of PC-positive cells. Specifically, AT/RT-TYR demonstrated the highest percentage of ciliated cells. Knockdown of KIF3A significantly reduced cell proliferation and stem cell properties. Additionally, death receptor 5 signaling was significantly up-regulated. Pharmacological inhibition by Ciliobrevin D phenocopied these results, specifically after induction of primary ciliogenesis through serum starvation. In a fly model of SMARCB1 deficiency, concomitant knockdown of several cilia-associated genes resulted in a substantial shift of the lethal phenotype with >20% of flies reaching adulthood. In conclusion, these results implicate PC as a key feature of AT/RT biology and suggest primary ciliogenesis as a potential therapeutic target, especially in AT/RT-TYR.